Storage of pink perch Nemipterus japonicus) in ice : Chemical, microbiological and sensory assessment - Reddy, G Vidya Sagar; Srikar, L N (Indian Journal of Fisheries, 2011)
The most important objective in postharvest techftology of fish is to preserve its freshness. Many tropical fishes have longer shelf life when s:tored in ice than those from tonperate water;: because of lowÂ» number of psychotrophs (Disney et al. 1971). The storage life of marine fish in ice varies between 9 and 21 days (Bramstedt 1965). According to Boyd and Wilson (1978), for every hour fishes are held on deck at temperature between 14*C and 18*C, they loose the equivalent of one day shelf life in ice.